Augmented Reality in Fashion Retail: Enhancing Consumer Decision-Making and Engagement - Dandawate, Sankalp; Khanna, Palak; Gawande, Amol; Kumar, Atul; Shukla, Stuti (Mercados y Negocios, 2025)
The present study investigated the impact of Augmented Reality (AR) across consumers in the fashion industry by examining the role of AR strategies in the purchasing routine of consumers in India, investigating the impact of AR technologies on the digital populace, and exploring the factors associated with the purchasing decision. In addition, the effect of AR on consumer engagement is illustrated. A quantitative methodology research approach was applied, and data were collected from 200 consumers using a purposive sampling technique with the aid of a structured questionnaire. The quantitative data were analysed using the SPSS tool version 23 package by performing ANOVA, frequency, and correlation analysis. The outcomes of the study revealed that perceived benefits of AR, likely authenticity, and return rates impact consumer decision-making strategies. Furthermore, discovered the determinants to improve the buyer’s decision effectively. The research study implies that the brands should adopt AR strategies to integrate with the values and choices of consumers to nurture a sustainable association. Overall, the study recommends effective implementation of AR technologies to provide enhanced shopping experiences through the amalgamation of physical atmosphere and digital systems.